A Review on harmonics elimination in real time for cascaded H-bridge multilevel inverter using particle swarm optimization - Muhammad Tayyab Yaqoob; Mohd Khairil Rahmat; Siti Marwangi Mohamad Maharum; Mazliham Mohd. Su’ud (Institute of Advanced Engineering and Science, 2021)
Renewable energy has a great importance for power generation as it does not use the fossils fuels. Energy generated from alternative energy sources are weather dependent. To generate a continuous power to meet the load requirements, Battery energy storage system are used. Power conversion process must be much efficient as possible to convert the DC stored energy into AC. This conversion process is usually done by the help of inverters. This paper gives the brief overview on three main categories of multilevel inverter like cascaded h-bridge, neutral point clamped and flying capacitor multilevel inverter and highlights their advantages which can also help the scholars to deeply explore the categories of multilevel inverter. Harmonic elimination is usually done by controlling the switching angles of the inverter. Among all the switching angles techniques, selective harmonic elimination pulse width modulation (SHEPWM) technique is widely used, that has also discussed in this paper. Furthermore, to eliminate the harmonics using SHEPWM, it has the set of nonlinear transcendental equations, these set of equations can be effieceintly solved by the optimization methods. The most efficient and reliable optimization method like particle swarm optimization has been discussed with multiple objective functions in this paper. This paper will help the scholars to understand the finest category of multilevel inverter for harmonic elimination in terms of efficiency and output quality.